2020
DOI: 10.24065/2237-9460.2020v10n0id1143
|View full text |Cite
|
Sign up to set email alerts
|

Opiniões de mães e profissionais sobre a sexualidade de pessoas com deficiência intelectual

Abstract: O objetivo deste estudo é investigar sobre a sexualidade de pessoas com deficiência intelectual, segundo a perspectiva de profissionais e familiares que convivem com essa realidade. A pesquisa de natureza qualitativa foi realizada com três profissionais e três responsáveis por pessoas adultas com deficiência intelectual. Os resultados indicam que existem alguns mitos em relação ao assunto que não se confirmam na prática, havendo a necessidade de superação desses mitos. Conclui-se que a sexualidade é a mais nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
1
Order By: Relevance
“…Studies indicate that individuals with intellectual disabilities are more likely to lose custody of their children, even when there is social and family support (Tilley et al, 2012). From a Brazilian cultural perspective, previous studies revealed that these individuals are considered to have less capacity to raise children (Gonçalves & Barbosa, 2020). This result shows the relevance of this information for professionals working with people with intellectual disabilities to provide information about parenting practices for both parents and individuals with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicate that individuals with intellectual disabilities are more likely to lose custody of their children, even when there is social and family support (Tilley et al, 2012). From a Brazilian cultural perspective, previous studies revealed that these individuals are considered to have less capacity to raise children (Gonçalves & Barbosa, 2020). This result shows the relevance of this information for professionals working with people with intellectual disabilities to provide information about parenting practices for both parents and individuals with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that individuals with intellectual disabilities are more likely to lose custody of their children, even when there is social and family support (Tilley et al, 2012). From a Brazilian cultural perspective, previous studies revealed that these individuals are considered to have less capacity to raise children (Gonçalves & Barbosa, 2020). This result…”
Section: Reproduction Parenting and Sterilisationmentioning
confidence: 99%
“…Os debates sobre as questões de gênero e sexualidade são emergentes (HANSON;RICHARDS, 2021;KUNIN, 2021;MELO, 2021) e, ainda, são um tabu, especialmente quando se trata de pessoas com deficiência, os debates podem ficar ainda mais restritos, até causando incômodo para alguns educadores (ORTOLAN et al, 2020;BARBOSA, 2020;PRIOSTE, 2010). As dificuldades em discutir esse tema são históricas, desde o início do século XX Freud já expressava preocupações com o esclarecimento sexual das crianças.…”
Section: Introductionunclassified